The political economy of inequality - Stilwell, Frank J. B. (Cambridge, U.K. : Polity, 2019)
"Economic inequality has become a defining issue of our age. This book, written by leading political economist Frank Stilwell, provides a comprehensive overview of the nature, causes, and consequences of the growing divide between rich and poor - and shows how there are alternative public policies that could help bridge this gap"--
Mind the gap -- Incomes, wealth, poverty and equity -- Scales and shapes of inequality -- Shifting shares -- Multi-dimensional inequalities -- Explaining who gets what -- Driving the disparities -- Hazards to handle: opportunities to grasp -- Towards happier societies? -- Redistribution -- Progressive pre-distribution -- A global challenge -- Impediments to equity -- Making the future.
Includes bibliographical references and index.
Keywords: Income distribution; Equality